Pravo na obrazovanje i roditeljska odgovornost / The Right to Education and Parental Responsibility - Vranić, Džamna; Balić, Lejla (Pregled: časopis za društvena pitanja / Periodical for social issues, 2025)
The right of the child has become, in the civilizational development to which modern states, United Nations members belong, one of the key contents of building a new and better world order. This means that, from birth until full legal capacity, the child enjoys and must enjoy the rights corresponding to the duties of parents and guardians, and the political community at various levels. Such rights and duties are determined by international conventions and other documents that are binding for all United Nations members. Regardless of differences in the cultural, political and economic circumstances of individual United Nations members, there are universal rights of the child and, consequently, universal duties in every legal system. This paper clearly presents that the provisions of the international political order oblige the state of Bosnia and Herzegovina to eliminate the current state of insufficient implementation of its duties specified in its Constitution.